A-Z of nutritional supplements: dietary supplements, sports nutrition foods and ergogenic aids for health and performance: Part 44 - Senchina, D. S.; Stear, S. J.; Burke, L. M.; Castell, L. M. (British Journal of Sports Medicine, 2013)
Part 44 is dedicated to a review on supplements used in the sport and exercise arena for weight loss, with a particular focus, including a utilitarian and novel classification, on the wide assortment of herbs used as the active ingredient(s), particularly in the seemingly fashionable supplements marketed as having `thermogenic` properties.